Strategi Pengembangan Kurikulum Menghadapi Tuntutan Kompetensi Abad 21 - Asy’ari, Ary; Hamami, Tasman (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2020)
The purpose of this study is to find out how the curriculum development strategy in dealingwith the demands of the 21st century, curriculum development according to David Pratt andWinarno Surahmad are more conceptual than material which includes the activities ofcompiling, implementing, evaluating and refining the curriculum. The research method in thisresearch is the study of literature or literature studies by finding various sources of data derivedfrom relevant books and journal articles that are useful to strengthen the argument of the authorThe results showed that the curriculum development strategy can be carried out with severalsteps, namely: identification of needs, searching curriculum materials, curriculum materialanalysis, curriculum material assessment, decision making adoption of curriculum material.